Focus on 14 sewage treatment plants in the Mpumalanga Province, South Africa in order to gauge the efficiency of wastewater treatment - Samie, A; Obi, C L; Ingumbor, J A; et al (My University, 2009)
In order to identify the treatment methods used in different sewage treatment plants (STPs) in the Mpumalanga Province and to determine the efficiency of wastewater treatment by these plants, municipal STPs were surveyed, and raw and treated wastewater samples collected. A total of 14 STPs were visited and the collected samples were analysed for physicochemical and microbiological parameters using standard methods. The treatment methods identified included ponds, activated sludge and trickling filters. The reduction of turbidity by the plants varied between 6.2 and 99.6% while conductivity, pH and temperature varied slightly between the influent and the effluent wastewater. Thirteen (92.8%) of the plants used chlorine for disinfection of the final effluent, however only 2 (14.2%) of the plants managed to produce effluent with 0 (zero) faecal conforms per 100 m€. Common pathogenic bacteria isolated from the final effluent included Salmonella, Shigella, Escherichia coli, Vibrio spp. and Enterococcus spp. The final effluent was used for irrigation and recycling purposes in 4 plants, all the other treatment plants discharged the effluent into the river or to the environment. The present study indicated that there is a move toward the renovation of wastewater treatment by the municipalities in the Mpumalanga Province with the adoption of biological treatment. All the STPs reduced the turbidity of wastewater as well as the different microbial indicators counts; however, several pathogenic bacterial organisms could still be detected in the final effluent. Further studies are needed to confirm the role of the treatment procedures on nutrient reduction and elimination of other viral and parasitic pathogens by the sewage treatment plants.
PK
Keywords: Sewage/microbiology; Waste Water; Water Pollution